(untitled) (Jurnal Desain Komunikasi Visual Nirmana, 2006)
The research explores the issue of graffiti especially artistic graffiti that recently has been developing rapidly in Surabaya. The research purpose is to expose scientifically the motivation behind the creation of graffiti from the creator (known in the graffiti community as bomber) point-of-view and its relation with the cityÂ’s needs. The research also provides a scientific argument on graffiti contribution to the cityÂ’s social development. The research uses qualitative method based on grounded theory. Abstract in Bahasa Indonesia : Penelitian ini mengangkat masalah graffiti terutama graffiti artistik yang kini mulai berkembang di Surabaya. Tujuan penelitian adalah menemukan secara ilmiah motivasi pembuat graffiti (disebut bomber) dalam membuat graffiti di Surabaya%2C menghubungkan keinginan bomber dalam berkarya dengan kepentingan kota dan memberikan argumentasi ilmiah tentang partisipasi graffiti dalam perkembangan sosial kota. Metode penelitian adalah kualitatif yang menggunakan rancangan penelitian grounded theory. graffiti%2C ecology%2C socio-cultur%2C artistic%2C Surabaya.